Analysis the Development Strategy of Arabic Education Department in IAIN Curup - Yasmar, Renti; -, Miftahul Huda; Sulaikho, Siti; Anwar, Mohammad Shohibul; Maghfiroh, Rodiatul (Institut Agama Islam Negeri (IAIN) Kediri, 2021)
In order to make continuous improvements and build a culture of quality in universities, especially in the implementation and development of study programs, each university should develop a strategy for developing study programs. Program development strategy is an important factor in the review or assessment of study program accreditation to determine the development of study programs that are in accordance with the National Higher Education Standards. (SN Dikti). The method used in this study is a situation analysis using a SWOT analysis based on the performance indicators of the Study Program Management Unit or UPPS, which in this case is the Tarbiyah Faculty of IAIN Curup and the indicators of the study program, namely the IAIN Curup Arabic Language Education study program. Data analysis is presented in the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. The purpose of this study is to measure the position of the existence of the study program on the External Internal (IE) matrix, so that it can be used as a basis in formulating strategies for the development of the IAIN Curup Arabic language education study program. The results of the IE matrix measurement show that the IAIN Curup Arabic language education study program is in a growth position, with an IFE result of 3.2 and an EFE matrix of 3,045. The development strategy of the IAIN Curup Arabic language education study program based on the results of the analysis focuses on 4 activities, namely: Study program development, Study program penetration, Product Integration and Development. Keywords: Development Strategy; SWOT Analysis; Arabic Education Department